Moving beyond the enduring dominance of positivism in psychological research: Implications for psychology in Australia - Breen, Lauren; Darlaston-Jones, D. (John Wiley & Sons Ltd., 2010)
Almost since its inception, the dominant narrative of modern psychology has embraced positivism through its insistence that psychological science is objective, generalisable, and value free (or neutral). Consequently, quantitative research and, in particular, experimental designs, are privileged over other forms of enquiry, and other epistemologies, ethodologies, and methods remain marginalised within the discipline. We argue that the enduring hegemony of positivism needs to be opposed to enable psychology to genuinely understand the antecedents of, and provide meaningful sustainable solutions for, complex human issues without being constrained by a narrow focus on method. We discuss the ways in which psychology in Australia can move towards embracing a constructionist epistemology that provides the framework for methodological pluralism. We provide a number of suggestions for change across the interrelated areas of accreditation, curriculum, the Australian Psychological Society, and research.